All‐Nanofiber‐Based Janus Epidermal Electrode with Directional Sweat Permeability for Artifact‐Free Biopotential Monitoring. Issue 12 (29th January 2022) - Yang, Xianqing; Wang, Shuqi; Liu, Mengyuan; Li, Lianhui; Zhao, Yangyong; Wang, Yongfeng; Bai, Yuanyuan; Lu, Qifeng; Xiong, Zuoping; Feng, Simin; Zhang, Ting
Abstract: Epidermal electronics have been developed with gas/sweat permeability for long‐term wearable electrophysiological monitoring. However, the state‐of‐the‐art breathable epidermal electronics ignore the sweat accumulation and immersion at the skin/device interface, resulting in serious degradation of the interfacial conformality and adhesion, leading to signal artifacts with unstable and inaccurate biopotential measurements. Here, the authors present an all‐nanofiber‐based Janus epidermal electrode endowed with directional sweat transport properties for artifact‐free biopotential monitoring. The designed Janus multilayered membrane (≈15 µm) of superhydrophilic‐hydrolyzed‐polyacrylonitrile (HPAN)/polyurethane (PU)/Ag nanowire (AgNW) can quickly (less than 5 s) drive sweat away from the skin/electrode interface while resisting its penetration in the reverse direction. Along with the medical adhesive (MA)‐reinforced junction‐nodes, the adhesion strength among the heterogeneous interfaces can be greatly enhanced for robust mechanical‐electrical stability. Therefore, their measured on‐body electromyography (EMG) and electrocardiography (ECG) signals are free of sweat artifacts with negligible degradation and baseline drift compared to commercial Ag/AgCl gel electrodes and hydrophilic textile electrodes. This work paves a way to design novel directional‐sweat‐permeable epidermal electronics that can be conformally attached under sweaty conditions for long‐term biopotential monitoring and shows the potential to apply epidermal electronics to many challenging conditions. Abstract : A directional‐sweat‐permeable epidermal electrode offers a promising pathway towards artifacts‐free biopotential monitoring. The obtained skin‐conformable 15‐µm‐thick electrode can quickly drive sweat away from the skin/electrode interface while resisting its penetration in the reverse direction. They can steadily and accurately record on‐body electromyography and electrocardiography signals with negligible degradation and baseline drift under sweaty conditions.